Short‐term impact of Altmetric Attention Scores on citation counts in selected major pharmacy journals. Issue 1 (25th June 2019) - Dixon, Dave L.; Baker, William L.
Abstract: Introduction: The impact and quality of a faculty member's publications is a key factor in promotion and tenure decisions. The Altmetric Attention Score (AAS) is an objective score frequently used to determine the reach of a published work across the World Wide Web and social media. The utility of the AAS in pharmacy practice journals is not well understood. Objective: To determine the short‐term impact of a higher AAS on citation count for articles published in major pharmacy journals. Methods: This cross‐sectional study evaluated articles from pharmacy journals ranked in the top 10% according to the AAS in the year 2017. Individual sources of attention that determined the AAS were also evaluated. Correlation between the AAS and the number of citations (through November 2018) was assessed using the Spearman's correlation (rs ) test. A Kruskal‐Wallis one‐way analysis of variance was used to compare the AAS between journals. Results: Six major pharmacy journals were identified. A total of 1376 articles were published in 2017, and 137 of these represented the top 10% with the highest AAS. The median AAS was 19 (interquartile range 15‐28). Twitter.com and Mendeley.com were the most common sources of attention. Over half (56.2%) of the articles were original investigations and 49.8% were either cross‐sectional, qualitative, or cohort studies. No significant correlation was found between the AAS and citation count ( r s = 0.07, P = .485). Mendeley was the only attention source that correlated with the number of citations ( r s = 0.486, P  < .001). The median AAS varied widely between each journal ( P  < .001). Conclusions: The median AAS of 19 suggests articles published in selected major pharmacy journals are near the top 5% of all scientific output. However, we found no short‐term correlation between the AAS and the number of citations for articles published in major pharmacy journals in the year 2017.